Colonial pressure and indigenous claim in Cajamarca (1785-1820) according to the archive of the "Protector of natives" - Lavalle, Bernard (1990)
For some fifteen years now, the increasingly frequent recourse to local archives has been one of the dominant characteristics of the new orientations of Peruvian historiography on the colonial era. Thus, the analyzes hitherto founded and structured essentially from repositories preserved in Lima or Seville were renewed, vivified and nuanced. Interestingly, in such a context, Cajamarca, which was in Spanish times the head of a district that was both large, populated and active —in fact the true capital of the northern Andes despite the colonial decision to establish on the coast, in Trujillo, the seat of the bishopric—does not seem to have sparked the investigations that it obviously deserves and is possible given the wealth of its remarkably classified and well-preserved departmental archive.